ЕКОНОМСКА ОБЕЛЕЖЈА КОРИШЋЕЊА БИОГАСА ЗА ПРОИЗВОДЊУ ЕЛЕКТРИЧНЕ И ТОПЛОТНЕ ЕНЕРГИЈЕ - Јовановић, Миленко; Тица, Недељко; Зекић, Владислав; Марковић, Тодор; Милић, Драган (Economics of Agriculture, 2011)
Biogas is a common name for the mixture of gases derived from anaerobe fermentation of the organic matter. Production of biogas, in case of some consumers, can cover larger part of energetic needs by increasing energetic independence individual consumers and society. In addition, in this way reduces pollution and protects the environment. Due to the need to increase the consumption of renewable energy sources the state has adopted incentives for the production of electricity using renewable energy sources. Economic analysis of investment in plant to produce electricity and heat production shows that achieved a signifcant level of cost, while investments due to the high proftability of investment is relatively low. In accordance with the time required by the state institutions to provide adequate support measures should not be limited only on price support.